Impact of media literacy on soft drink consumption among adolescents in Klang Valley, Malaysia - Mohammad Shahid, Nur Nadirah (2014)
Food and beverage advertisements could influence adolescents‟ food choices and affect their healthy diet. The influence of advertisements is getting worse when the marketers use misleading messages in soft drink advertisements to attract adolescents. For instance, media literacy was found to be a preventive measure in saving culture from being misled by soft drink advertisements, and therefore four objectives were proposed for this study. Firstly, this study determined soft drink intake among adolescents in Klang Valley area. The second objective was determined media literacy score and level among adolescents towards soft drink advertisement. Next, the third objective was to investigate the relationships between attitudes, subjective norms and perceived behavioural control and the intention of soft drink consumption among adolescents. Lastly, the last objective was aimed at identifying the relationships between attitudes, subjective norms, perceived behavioural control, the intention of soft drink consumption and media literacy score among adolescents in Klang Valley. A cluster sampling method was used in collecting data within Klang Valley area. A total of 500 questionnaires were distributed to adolescents aged between 13 to 18 years old at selected secondary schools in Klang Valley. Two main scales utilised were Theory of Planned Behaviour (TPB) scale and Media Literacy (ML) scale. The descriptive, exploratory factor analysis, multiple linear regression, and Pearson product-moment correlation analyses were carried out to answer the research objectives. Results revealed that 36% of respondents drank a minimum of 1 can, bottle or glass of soft drink for the past seven days and possessed good level of media literacy (45.1%). Meanwhile, the TPB constructs explained 14% of variance in adolescents‟ intention of soft drink consumption. In addition, the total media literacy score towards soft drink advertisement was significantly positive to correlate with attitude (r = 0.250, p<.01) and subjective norms (r = 0.174, p<.01). Conversely, total media literacy was significantly negative to correlate with intention to consume soft drink (r = -0.19, p<.01) and indicated that media literacy could lower the intention to consume soft drink, thus reduce soft drink consumption among adolescents. Several implications were highlighted to the authorities including Ministry of Health to better understand the trend of soft drink consumption. These implications were also proposed to Ministry of Education to create awareness on media literacy and consider the idea to safeguard and prevent adolescents from being misled by the media, especially on unhealthy food and beverage advertising. Moreover, the findings of this study were hoped to also help soft drink marketer and producers to understand media literacy and adolescents‟ soft drink consumption behavior. Other than that, recommendations for future research including using semi-structure in-depth personal interview or focus group were suggested to yield more in-depth data. Finally, it was suggested that future studies should include adolescents in both urban and rural areas in Malaysia, to better enable generalisation of findings.